2014 Proceedings of the SICE Annual Conference (SICE) 2014
DOI: 10.1109/sice.2014.6935296
|View full text |Cite
|
Sign up to set email alerts
|

A proposal of Fault Tree Analysis for control programs

Abstract: This paper proposes a method of Fault Tree Analysis (FTA) for control program. If malfunction of control program occurs, industrial product into which program is installed may behave inadequately. As a result, it causes some faults for industrial products, but it also causes damages to the users and environments. This paper proposes following method; prepare FT templates corresponding to the program structure, extract characteristics of control program, and develop FT according to the predefined rules. As a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Junga et al [28] proposed an automatic FT development method from software specifications written in formal specification language called NuSCR. From the results of [24] and [25], we found that the causes of the undesirable events are detected at the program level by using FT. By improving this function, FTA for various types of CSWs becomes able to conduct.…”
Section: Related Workmentioning
confidence: 97%
See 1 more Smart Citation
“…Junga et al [28] proposed an automatic FT development method from software specifications written in formal specification language called NuSCR. From the results of [24] and [25], we found that the causes of the undesirable events are detected at the program level by using FT. By improving this function, FTA for various types of CSWs becomes able to conduct.…”
Section: Related Workmentioning
confidence: 97%
“…Leveson et al [24] prepared an FT template corresponding to the programming language instruction and developed an FT by combining those FT templates. Takahashi et al [25] proposed an automatic FT development method by expanding Leveson's idea. Kumar et al [26] showed that in the development of safety-critical ball position control systems, adequate CSW design could be achieved when the FTA was conducted in the software development life cycle's proper timing.…”
Section: Related Workmentioning
confidence: 99%
“…However, as the method of combining the FT templates to develop an FT is not defined, the level of completeness of the FT is dependent on the ability of the analyst. Therefore, Takahashi et al proposed rules for combining FT templates and developing an FT while reverse-tracking the process in which faults occur [14]. Park et al, with regard to a nuclear power plant control system developed using a Function Block Diagram with a Programmable Logic Controller, proposed a method in which the FT is developed by preparing and combining FT templates in relation to the Function Block [15].…”
Section: Related Workmentioning
confidence: 99%
“…Leveson et al showed that the Fault Tree (FT) could be developed by preparing the FT templates corresponding to the essential instructions of the ECSW and combining those FT templates [11,12]. Takahashim, et al proposed the development rules that developed FT automatically by tracing the process that caused the accident and combining the FT templates [13]. Pai et al proposed the method that calculated the reliability of the system by inputting the design specifi cations written in the UML [14].…”
Section: Introductionmentioning
confidence: 99%